Cigarette smoke is a risk factor for severity and treatment outcome in patients with culture-positive tuberculosis - Chuang HC; Su CL; Liu HC; Feng PH; Lee KY; Chuang KJ; Lee CN; Bien MY (Dove Medical Press, 2015)
Hsiao-Chi Chuang,1,2,* Chien-Ling Su,1,2,* Hui-Chiao Liu,2 Po-Hao Feng,1,3 Kang-Yun Lee,1,3 Kai-Jen Chuang,4,5 Chun-Nin Lee,1,2 Mauo-Ying Bien2,6 1Division of Pulmonary Medicine, Department of Internal Medicine, Shuang Ho Hospital, Taipei Medical University, New Taipei, 2School of Respiratory Therapy, 3Department of Internal Medicine, 4Department of Public Health, School of Medicine, College of Medicine, 5School of Public Health, College of Public Health and Nutrition, 6Division of Pulmonary Medicine, Department of Internal Medicine, Taipei Medical University Hospital, Taipei, Taiwan *These authors contributed equally to this work Objective: Smoking has been associated with tuberculosis (TB); however, the effects of smoking on the effectiveness of TB treatment remain unclear.Materials and methods: Data were retrieved from case notes and interviews of subjects registered in the TB-reporting system from 2010 to 2012. Study cases were defined as subjects with TB-positive sputum cultures, whereas the controls were defined as subjects with non-TB-related pulmonary diseases. Statistical analyses included logistic regression and multivariate Cox proportional hazard regression models.Results: A total of 245 cases with cultures positive for TB and 114 controls with non-TB-related pulmonary diseases and negative sputum cultures were recruited. Current smokers had the highest failure rate (33%) for TB treatment, and they had the most severe pulmonary lesions based on chest X-ray grading. Current smokers had a 1.36-fold (95% confidence interval 1.03–2.36, P<0.05) higher odds ratio for cultures positive for TB compared with nonsmokers. In subjects with TB-positive cultures, current smoking was associated with an increase in treatment days required for cultures to convert from positive to negative (hazard ratio 1.12, 95% confidence interval 1.03–1.39; P<0.05).Conclusion: Longer periods of treatment may be required for TB patients who are current smokers. Keywords: Mycobacterium tuberculosis, cigarette, immunity, chest X-ray